2023
DOI: 10.3390/vaccines11020355
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Post-Vaccination Longitudinal Follow-Up of Quantitative SARS-CoV-2 Anti-Spike Total Antibodies in Health Care Professionals and Evaluation of Correlation with Surrogate Neutralization Test

Abstract: Numerous vaccines have been generated to decrease the morbidity and mortality of COVID-19. This study aims to evaluate the immunogenicity of the heterologous boosts by BioNTech against homologous boosts by CoronaVac at three-month intervals in two health care worker (HCW) cohorts, with or without prior COVID-19, for one year post-vaccination. This is a prospective cohort study in which the humoral responses of 386 HCWs were followed-up longitudinally in six main groups according to their previous COVID-19 expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Consistent with others ( 16), anti-spike IgG antibodies persisted but at moderately low levels following CoronaVac vaccination. Vaccination resulted in substantial increase in the S-IgG levels, surpassing those observed in participants without prior exposure, aligning with the concept that hybrid immunity provides a more robust immune response, described in other studies (17)(18)(19). This study adds to others that showed CoronaVac's ability to generate potent antibodies against SARS-CoV-2 (17,19), underscoring the importance of boosting, providing evidence of CoronaVac ability to elicit long-lasting anti-spike antibodies against SARS-CoV-2.…”
Section: Table 2 Seroconversion Ratessupporting
confidence: 87%
“…Consistent with others ( 16), anti-spike IgG antibodies persisted but at moderately low levels following CoronaVac vaccination. Vaccination resulted in substantial increase in the S-IgG levels, surpassing those observed in participants without prior exposure, aligning with the concept that hybrid immunity provides a more robust immune response, described in other studies (17)(18)(19). This study adds to others that showed CoronaVac's ability to generate potent antibodies against SARS-CoV-2 (17,19), underscoring the importance of boosting, providing evidence of CoronaVac ability to elicit long-lasting anti-spike antibodies against SARS-CoV-2.…”
Section: Table 2 Seroconversion Ratessupporting
confidence: 87%
“…Khoury and co-workers, analyzing the relationship between in vitro neutralization level and the protection produced by either seven different vaccines or natural infection found that the neutralization level was highly predictive of immune protection [65] . This and other studies underline the relevance of the quantification of NAbs for a number of purposes and to find sensitive and specific assays to be used on large scale [70] [72] .…”
Section: Overview On Serological Detectionmentioning
confidence: 61%
“…These findings highlight the importance of the humoral response in COVID-19. A recent study shows that a heterologous booster of BioNTech mRNA vaccine induces a robust immune response and antibody durability, regardless of previous infection history or not [37] , [38] . It has been described that administration of a third dose of BioNTech mRNA vaccine induced a strong immune response in all age groups and regardless of prior COVID-19 infection status [39] …”
Section: Discussionmentioning
confidence: 99%